Contributions of meetings of awareness and care for nursing students - Luciara Fabiane Sebold; Silvana Silveira Kempfer; Telma Elisa Carraro; Vera Radünz (Universidade Federal de Santa Maria, 2012)
Objective: to report the contributions awareness meetings and care provided to nursing students at a public university in southern Brazil. Method: qualitative Research for Convergent Care approach (PCA), developed with 42 nursing students in a public university in Southern Brazil. Data collection occurred during four meetings. Data analysis followed PCA. Results: the students were able to experience a relaxed space with recreational activities which have brought the expression of everyday practices, raise awareness of caring for themselves and care for others. Conclusions: reflect on the reality, critically creative, is the best way to get the expression of the potential beyond the reflection and transformation of some concepts of everyday nursing